Hubungan Penggunaan Masker Terhadap Tingkat Kejadian Akne Vulgaris Pada Tenaga Kesehatan di RS Royal Prima Medan - Melisa Aprilya Simanjuntak; Widyaningsih oentari; Rudi Chandra (Dinasti Research, 2024)
Acne vulgaris is a common skin condition with a prevalence of around 85-100%, frequently encountered in Indonesia. Prolonged use of masks can lead to continuous friction on the facial skin, triggering irritation and inflammation. The aim of this study is to examine the relationship between mask usage and the incidence and severity of acne vulgaris among healthcare workers at RS Royal Prima Medan. This research is an analytical observational study employing a quantitative approach with a cross-sectional design. The study was conducted at RS Royal Prima Medan from January 2024 to June 2024. The population of this study consists of healthcare workers at RS Royal Prima Medan, with 69 individuals selected as the sample. The results indicate a relationship between the duration of mask use and the incidence of acne vulgaris; a relationship between the type of mask and the incidence of acne vulgaris; a relationship between daily facial wash use and the incidence of acne vulgaris; a relationship between the frequency of facial cleansing with facial wash and the incidence of acne vulgaris; a relationship between replacing masks and the incidence of acne vulgaris; and a relationship between the occurrence of acne vulgaris and mask use with the incidence of acne vulgaris.